Opportunities for Nanomedicine in Clostridioides difficile Infection - Pei-Wen Wang; Wei-Ting Lee; Ya-Na Wu; Dar-Bin Shieh (MDPI AG, 2021)
Clostridioides difficile, a spore-forming bacterium, is a nosocomial infectious pathogen which can be found in animals as well. Although various antibiotics and disinfectants were developed, C. difficile infection (CDI) remains a serious health problem. C. difficile spores have complex structures and dormant characteristics that contribute to their resistance to harsh environments, successful transmission and recurrence. C. difficile spores can germinate quickly after being exposed to bile acid and co-germinant in a suitable environment. The vegetative cells produce endospores, and the mature spores are released from the hosts for dissemination of the pathogen. Therefore, concurrent elimination of C. difficile vegetative cells and inhibition of spore germination is essential for effective control of CDI. This review focused on the molecular pathogenesis of CDI and new trends in targeting both spores and vegetative cells of this pathogen, as well as the potential contribution of nanotechnologies for the effective management of CDI.